PENERAPAN ASPEK TEKNIS PEMELIHARAAN SAPI POTONG DI DESA BAGAN SINEMBAH KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILIR - Imran Saherman; Dewi Febrina; Hidayati Hidayati (Jurnal Peternakan, 2007)
This research aims to investigate applied tehnical aspects of farmers keeping beef cattle in Rokan H:i1ir Regency, consists; breed selection. feed giving, management housing, health management and keeping management. This research was done in july '1fX!7 in Bagan Sinembah Village, Rokan Hilir Regency, Riau Province with survey method. Data was collected by using, simple random sampling and descriptive analyze used to know percentage, mean and standard deviation. The result of this study was showed that farmers in Bagan Sinembah Village not good applied tehnical aspects of keeping management beef cattle because they were assumsed., keeping beef cattle just as a job side, a saving and keeping management was done by traditional withekstensifsystem.